Hepatitis C infection and hepatocellular carcinoma in liver transplantation: a 20‐year experience. Issue 9 (14th March 2013) - Dumitra, Sinziana; Alabbad, Salleh I.; Barkun, Jeffrey S.; Dumitra, Teodora C.; Coutsinos, Dimitrios; Metrakos, Peter P.; Hassanain, Mazen; Paraskevas, Steven; Chaudhury, Prosanto; Tchervenkov, Jean I.
Abstract Background Hepatitis C infection (HCV) and hepatocellular carcinoma (HCC), the two main causes of liver transplantation (LT), have reduced survival post‐LT. The impact of HCV, HCC and their coexistence on post‐LT survival were assessed. Methodology All 601 LT patients from 1992 to 2011 were reviewed. Those deceased within 30 days (n = 69) and re‐transplants (n = 49) were excluded. Recipients were divided into four groups: (a) HCC‐/HCV‐(n = 252) (b) HCC+/HCV‐ (n = 58), (c) HCC‐/HCV+ (n = 106) and (d) HCC+/HCV+ (n = 67). Demographics, the donor risk index (DRI), Model for End‐Stage Liver Disease (MELD) score, survival, complications and tumour characteristics were collected. Statistical analysis included anova, chi‐square, Fisher's exact tests and Cox and Kaplan–Meier for overall survival. Results Groups were comparable with regards to baseline characteristics, but HCC patients were older. After adjusting for age, MELD, gender and the donor risk index (DRI), survival was lower in the HCC+/HCV+ group (59.5% at 5 yrs) and the hazard ratio (HR) was 1.90 [95% confidence interval (CI), 1.24–2.95, P = 0.003] and 1.45 (95% CI, 0.99–2.12, P = 0.054) for HCC‐/HCV+. HCC survival was similar to controls (HR 1.18, 95% CI, 0.71–1.93, P = 0.508). HCC+/HCV‐ patients exceeded the Milan criteria (50% versus 31%, P < 0.04) and had more micro‐vascular invasion (37.5% versus 20.6%, P = 0.042). HCC+/HCV+ versus HCC+/HCV‐ survival remained lower (HR 1.94, 95% CI, 1.06–3.81, P = 0.041) after correcting for tumour characteristics and treatment. Conclusion HCV patients had lower survival post‐LT. HCC alone had no impact on survival. Patient survival decreased in the HCC+/HCV+ group and this appears to be as a consequence of HCV recurrence.